2016
DOI: 10.1007/s10916-016-0561-y
|View full text |Cite
|
Sign up to set email alerts
|

Applying Data Mining Techniques to Improve Breast Cancer Diagnosis

Abstract: In the field of breast cancer research, and more than ever, new computer aided diagnosis based systems have been developed aiming to reduce diagnostic tests false-positives. Within this work, we present a data mining based approach which might support oncologists in the process of breast cancer classification and diagnosis. The present study aims to compare two breast cancer datasets and find the best methods in predicting benign/malignant lesions, breast density classification, and even for finding identifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 35 publications
1
41
0
1
Order By: Relevance
“…In another study (17), Random Forest was demonstrated to have the best classification performance for the majority of the tested group, while in the case of masses texture, Naive Bayes had the best performance.…”
Section: Literature Reviewmentioning
confidence: 95%
“…In another study (17), Random Forest was demonstrated to have the best classification performance for the majority of the tested group, while in the case of masses texture, Naive Bayes had the best performance.…”
Section: Literature Reviewmentioning
confidence: 95%
“…The research paper done by Joana Diz Goreti Marreiros & Alberto Freitas [9] presents new computer based diagnosis system. By using this technique false positive diagnosis test can be reduced.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A decision support system with the employment of data mining approach which could assist oncologists to classify and diagnose breast cancer [31]. Two Portuguese-based binary class mammography datasets were used in this study and key features in the images were then selected using feature extraction.…”
Section: Other Breast Cancer Datasetsmentioning
confidence: 99%